Kajian Kesesuaian Pembangunan Ruko Terhadap Kebutuhan Pasar di Kota Mataram - Khatimah, Husnul (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
Activity increase in Mataram causes the increase of land demand for settlement and trades facilities. The demand doesn’t match by sufficient land availability, thus shop-house (ruko) is seen as solution to fulfill the needs of housing and trades facilities. But today, the existence of shop-house has become problem, people consider the over-scattered and idle shop-house doesn’t bring maximal services delivery. Those conditions as the main consideration of the research with aim measuring whether the shop-house development really meet the market needs or not. Results of analysis shows that the effectiveness of each shop-house, is just in effective level (not reached maximum/very effective), but the spatial policy implementation discrepancies are still found in the some distric. This condition is caused by the existence of shop-house located outside the trade area as well as the number of shop-houses already exceeds the market needs, resulting in a massive untapped shop. An excess amount of shop-house is caused by lack of government control in granting permission to construct the shop-house and the speculative motive of the owners of capital. Handling the shop-houses that have been built and exceed the needs can be done by applying spatial sanctions, ranging from a written warning, suspension service shop, site closure, revocation of permits, demolition, restoration of function space and administrative fines.